Effectiveness of Animated Video Education in Improving Knowledge and Attitudes towards Primary Dysmenorrhea Management among Students in Surabaya - Zhafirah Jihan Balqis Santoso; Indriatie; Miadi; Irine Christiany (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The incidence of menstruation indicates that physical maturity and the reproductive system have occurred in women. One of the disorders during menstruation is menstrual pain or primary dysmenorrhea. If primary dysmenorrhea is not treated, it will cause painful effects to reduce learning concentration which affects learning ability. Therefore, efforts that can be made to improve students' knowledge and attitudes in handling primary dysmenorrhea are by providing animated video education that is able to bring adolescents into an atmosphere of joy and joy. This study used the Pre-Experimental One Group Pretest-Posttest Design research design. The population is class X students at SMK Tri Guna Bhakti Surabaya. The research sample was 45 female students using random sampling techniques. Data collection used questionnaires and observation sheets, while data analysis used the Wilcoxon Signed Rank Test. The results of the Wilcoxon Signed Rank Test statistical test show a knowledge p value of 0.000 and an attitude of 0.001 which is less than the alpha limit determined by the researcher which is 0.05. There is an influence of animated video media on increasing the knowledge and attitudes of grade X students at SMK Tri Guna Bhakti Surabaya after being given an educational intervention for handling primary dysmenorrhea.